Perkembangan Bahasa dan Sastra Arab di Indonesia: Development of Arabic Language and Literature in Indonesia - Chamdar Nur; Kamaluddin Abu Nawas (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This research aims to identify the process of the entry of Arabic into Indonesia, analyze the contribution of Arabic to education and culture, and describe the development of Arabic literature in Indonesia historically and thematically. With a descriptive qualitative approach and historical analysis, this research uses primary data which includes manuscripts, yellow books and Arabic-Indonesian literary works, as well as secondary sources in the form of books, journals and related articles. Data collection techniques involve literature study, document analysis, and interviews with experts. Data analysis was carried out through content and historical analysis to trace the development of Arabic language and literature in Indonesia. The research results show that in the contemporary era, Arabic literature remains an integral part of the educational curriculum in Islamic institutions, such as Islamic boarding schools and universities. However, the focus of learning shifts from classical texts to an appreciation of modern Arabic literature. Many Arabic literary works have been translated into Indonesian, strengthening cultural ties between the Arab world and Indonesia. In addition, the translation of Indonesian literary works into Arabic is increasingly intensive, with Indonesian writers such as Habiburrahman El Shirazy and Taufiq Ismail introducing Indonesian literature to the Arab world. This phenomenon reflects the increasingly close reciprocal relationship between the two cultures.